Room-temperature formation of CdS magic-size clusters in aqueous solutions assisted by primary amines - Wushuang Wan (Nature Portfolio, 2020)
CdS magic-size clusters have, so far, been prepared only in organic solvents. Here, the authors report an aqueous-phase synthesis for CdS magic-size clusters at room temperature and reveal insights into the formation mechanism, including the key role of primary amines.